PENGARUH LATIHAN SHADOW DRILLING MENGGUNAKAN SHUTTLECOCK TERHADAP KETEPATAN PUKULAN SMASH PADA PEMAIN DI PB KAFIFA LAMPUNG TENGAH - Rake Yuzairi; Rachmi Marseilla Aguss (Journal of Physical Education, 2022)
The research method used in this study is an experimental research method. This method is used to determine whether there is an effect of the treatment carried out with shadow drilling exercises on the accuracy of smash hits in badminton games. In this case, what is being investigated is the effect of shadow drilling on the accuracy of the smash. The population used in this study were PB players. Central Lampung Kafifa. Sample According to Roscoe in the book (Sugiyono, 2013), for simple experimental research, successful research is with a small sample size between 10 to 20. Then the sample used is 20 players, totaling 20 males aged 13-15 years.From the results of data analysis, description, research results, and discussion conclusions can be drawn, namely: From the results of the t test it can be observed that t count is greater than t table (12.797 1.729) and a significant value of p is (0.000 0.05), these results explained that there was a significant difference between the pretest and posttest of Shadow Drilling on Smash Accuracy in PB Players. Central Lampung Kafifa. The average pretest data is 9.5 while the posttest is 15.7 with an increase of 6.2.